Pengaruh Psychological well-being dan Minat Belajar Terhadap Motivasi Belajar Siswa Kelas XI IPS Di SMAN 10 GOWA - Setiadi, Eko; Thalib, Syamsul Bachri; Mustafa, Mustafa (Prodi Bimbingan dan Konseling Fakultas Keguruan dan Ilmu Pendidikan | Universitas Islam As-Syafi'iyah, 2024)
The objectives of this research are to determine: 1) the description of students' psychological well-being, 2) the interest in learning among students in the class, 3) whether psychological well-being affects students' learning motivation, 4) whether interest in learning affects students' learning motivation, and 5) whether psychological well-being and interest in learning together affect students' learning motivation. The method used in this research is quantitative. The analysis employs statistical and econometric methods. The results of the research indicate that 1) the description of students' psychological well-being is high, 2) the description of students' interest in learning is at a moderate percentage based on the analysis conducted, and the indicator of enjoyable lessons is a highly desired indicator by students while learning, 3) partially, psychological well-being affects learning motivation, 4) partially, interest in learning affects students' learning motivation, 5) the coefficient of determination (R2) shows a positive relationship between psychological well-being (X1) and interest in learning (X2) on students' learning motivation.